Diplomacy of Dialogue: Pope Francis's Policy towards Islam and the Development of Interreligious Relations in the European Union - Piwko, Aldona (Journal for the study of religions and ideologies, 2025)
This article examines religious diplomacy as a political tool, focusing on Pope Francis' actions in shaping Christian-Muslim relations in the context of the integration challenges facing the European Union. The study focuses on the interfaith dialogue initiatives undertaken by the Holy See between 2013 and 2025 and their reception in the European Union member states. Based on an analysis of Catholic Church documents, papal speeches, diplomatic initiatives of the Holy See and the reactions of European institutions, the article shows that the "dialogue diplomacy" conducted by Pope Francis has been an important, yet often underestimated, political instrument influencing the perception of Islam in Europe, contributing to building a platform for cooperation between religious communities. The article argues that Pope Francis' approach to interfaith dialogue goes beyond the purely theological dimension, becoming part of a broader political strategy aimed at countering social polarization and promoting a model of integration based on mutual respect while preserving cultural identity. The study also highlights the challenges facing the pope's religious diplomacy in the context of growing tensions related to migration, the secularization of European societies, and political polarization in the countries of the European Union.